Food Insecurity in South Sudan: Solutions and Opportunities for Agricultural Transformation - Miteng, J. A.; Yuga, M. E (European Journal of Applied Sciences, 2024)
About 7.7 million people are facing acute malnutrition and need food assistance from the World Food Program. The major drivers of food insecurity in South Sudan are civil wars, political instability, communal conflict, and climate change. The increasing food and fuel prices, displacement, poor harvests, and high inflation continues to reduce households' purchasing power, with people unable to meet their basic needs. The objective of this research is to suggest solutions to alleviate food insecurity and increase food production and household incomes for smallholder farmers in Country. To get a better understanding of the food insecurity situation in South Sudan, multiple documents were reviewed including the Comprehensive Agriculture Master Plan (CAMP) for the Government of South Sudan and special reports. Despite the food insecurity in the country, huge opportunities such as large arable land, lengthy cropping seasons, diverse and nutritious crops, suitable land for livestock rearing, rivers with abundant fish exist in South Sudan. To maximize productivity, South Sudan needs to double food production through private and public partnership to enhance access to high quality inputs, improve extension service delivery, invest in tools and machines for opening up more arable land, a shift from using rudimental tools to mechanized agriculture. Improving Animal health and nutrition, commercializing livestock by introducing value addition technologies for livestock products i.e., milk, hides and skin, beef, and mutton. Strengthening the enabling policy environment and partnerships at community level through a private sector led initiative are vital. To the government needs to be supported, both financially and capacity wise, to review and implement the investment plan in CAMP. To enhance the growth of the private sector there is a need to design programs to sustainably transit from humanitarian to development.